AMELIORATIVE EFFECTS OF STEM BARK OF THE WONDER TREE, PROSOPIS CINERARIA (L.) DRUCE AGAINST LPS-INDUCED TOXICITY: AN IN VITRO STUDY - SHARMA, VEENA; SHARMA, PREETI (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present experimental investigation was planned to unravel and analyze the therapeutic potential of hydro-ethanol extract prepared from the stem bark of Prosopis cineraria against LPS-induced toxicity under in vitro conditions. Methods: Liver tissue samples from healthy Swiss albino male mice (Mus musculus) were used for the study. Liver homogenate (0.9 ml) was treated with 0.05 mg/ml of LPS along with 0.01 to 0.05 mg/ml of hydro-ethanol plant extract and allowed to incubate at 37˚C. The reactions were terminated at different time points at 0 min, 30 min, 1 h, 2 h, 4 h, 8 h and 24 h and alterations in oxidative stress (LPO, CAT, SOD, GSH, GST, and GPx) and biochemical parameters of hepatic toxicity (AST and ALT, ACP and ALP) were studied. Results: The results demonstrated that the obliterations in the levels of oxidative and biochemical parameters due to LPS induced toxicity were restored by the treatment with hydro-ethanol extract of Prosopis cineraria under in vitro conditions. The altered levels were biochemical parameters were observed at 0.05 mg/ml LPS concentration after 2 h; but administration of hydro-ethanol plant extract at concentration 0.04 mg/ml effectively reduced its level when compared to LPS treated samples under in vitro conditions Conclusion: The present research work unravelled the alleviating potential of a hydro-ethanol extract of Prosopis cineraria against LPS-induced toxicity by combating oxidative stress under in vitro environment.